About a possibility of creation of a deterministic unified mechanics - Khomyakov, G.K. (Вопросы атомной науки и техники, 2005)
The possibility of creation of a unified deterministic scheme of classical and quantum mechanics, allowing to
preserve their achievements, is discussed. It is shown that the canonical system of ordinary differential equation of
Hamilton classical mechanics can be added with the vector system of ordinary differential equation for the variables
of quantization. The interpretational problems of quantum mechanics are considered Обговорюється можливість побудови єдиної детерміністської механіки, яка зберігає досягнення
класичної і квантової механік. Показано, що в нерелятивістському випадку для досягнення цієї мети
канонічна система звичайних диференціальних рівнянь Гамільтонової механіки може бути доповнена
відповідною системою звичайних диференціальних рівнянь для змінних квантування. Обсуждается возможность построения единой детерминистской механики, сохраняющей достижения
классической и квантовой механик. Показано, что в нерелятивистском случае для достижения этой цели
каноническая система обыкновенных дифференциальных уравнений Гамильтона может быть дополнена
подходящей системой обыкновенных дифференциальных уравнений для переменных квантования.